Does Texas’ compensatory education funding get to the intended students? - Toenjes, Laurence A. (Education Policy Analysis Archives, 2021)
Two questions about Texas school expenditure patterns are examined. First, “How progressive are spending patterns among high and low poverty schools?” Second, “How unequal are expenditures per pupil between schools with at least 70% of their students classified as economically disadvantaged, in different districts?” The data, for school year 2017-2018, are restricted to 3,453 elementary and middle schools in 90 large Texas districts. The schools in each district were divided into high and low poverty groups. The differences in the average per pupil spending for operations between the two groups ranged from plus 1,382 in one district to a negative 802 in another. The average expenditures in schools with at least 70% economically disadvantaged students were 75% greater in one district than in another. It is demonstrated that districts with less extreme average levels of low-income students have more opportunity to act as good Samaritans, generally exhibiting substantially greater spending in their high poverty schools. This finding supports arguments for student funding weights that increase with increasing proportions of economically disadvantaged students. An incidental finding is that a commonly used measure of funding progressivity is a direct function of district and school level variances in poverty averages, and is therefore biased by them.